Analisis Pemahaman Guru Bahasa Inggris Terhadap Silabus dalam Implementasi Kurikulum Merdeka - Prima, Anggra; Reynaldy, Ainun Zasha Khairunniza; Nurwanaliyanti, Nurwanaliyanti; Setyani, Viera; Pratiwi, Nur Afni; Kurniawan, Muhammad Yahya Nuzulul (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
This research aims to analyze English teachers' understanding of the syllabus, its application in the learning process, and the obstacles in the context of implementing the independent curriculum. The method applied in this research is a qualitative-descriptive method. Data analysis uses the Miles Huberman analysis model. There were six informants for this research. This research was carried out at SDI Mutiara Islam Al-Ittiba, East Kutai. The research results show that the majority of English teachers have a sufficient understanding of the content and objectives of the Independent Curriculum syllabus. Teachers can measure the competencies that must be taught and prepare learning plans based on the syllabus. Meanwhile, implementation in the learning process is carried out by teachers developing or selecting teaching materials that are in the Independent Curriculum syllabus, encouraging the use of active and collaborative learning approaches, evaluating student achievement on an ongoing basis by the standards set in the syllabus, and reflecting on the learning process. that has been carried out and the evaluation results obtained. The obstacles in implementing the Independent Curriculum identify several obstacles faced by teachers in implementing the Independent Curriculum syllabus. Factors such as limited resources, a lack of adequate training, and a lack of clarity in curriculum implementation guidelines are the main obstacles to maximizing the potential of this curriculum. It is hoped that this research can make a positive contribution to efforts to improve the quality of English language teaching and learning in Indonesia.